The age of the Kagenfels granite (northern Vosges) and its bearing on the intrusion scheme of late Variscan granitoids - Hess, Jürgen C.; Lippolt, Hans J.; Kober, Bernd (Geologische Rundschau, 1995)
In the Saxothuringian part of the Vosges (France), a first series of Variscan plutonic rocks (diorites to granites) has been intruded by several younger granites. Rocks of both the older generations have been cross-cut by the late orogenic Kagenfels granite. The averages of the hitherto published mineral ages of the earlier rock generations are 331 and 334 Ma, respectively, whereas Rb-Sr and K-Ar dates around 290 Ma have been reported for the Kagenfels granite. Because of the unlikely large age hiatus, a redetermination of the intrusion age of the Kagenfels granite formation appeared to be irrevocable. The newly obtained mineral ages on the Kagenfels granite (K-Ar and 40Ar/39Ar biotite ages as well as single zircon radiogenic 207Pb/206Pb data: 331 ± 5 Ma) are about 40 Ma older than the previous results. They are interpreted as giving the time of emplacement of the Kagenfels granite during the latest Visćan. The mineral ages of the earlier plutonic rocks in this part of the Variscan Orogeny in all probability are not significantly different from their ages of intrusion. Therefore the age concordance of all three granitoid generations constrains a rather narrow time interval of orogenic magmatism close to the Lower-Upper Carboniferous boundary.